JAEPL, Vol. 22, Winter 2016-2017 - Joonna Smitherman Trapp; Brad Peters (Journal of the Assembly for Expanded Perspectives on Learning, 2017)
Editors’ Message Essays SPECIAL SECTION: DEEP READING STRATEGIES Jane Thompkins - Deep Reading Vajra Watson - Life as Primary Text: English Classrooms as Sites for Soulful Learning Tisha Ulmer - Using Pre-reading Strategies to Provide Historical Context in a Literature Course Grace Wetzel - ‘The Most Peaceful I Ever Felt Writing’: A Contemplative Approach to Essay Revision TEACHING AND LEARNING Kate Chaterdon - Contemplative Neuroscience and the Teaching of Writing: Mindfulness as Mental Training Ondine Gage - Resisting a Restrictive Discourse Policy J. Michael Rifenburg - The Performance of Literate Practices: Rhetoric, Writing, and Stand-up Comedy Rosanne Carlo - Getting Centered: A Meditation on Creating Pottery and Teaching Writing Robbie Clifton Pinter - The Transformative Practice of Writing and Teaching Writing Out of the Box Pamela B. Childers - Rattling Cages Book Reviews Julie Nichols - Threshold Concepts. Brad E. Lucas, et al. - Adler-Kassner, Linda, and Elizabeth Wardle, eds. Naming What We Know: Threshold Concepts of Writing Studies. Logan: Utah State University Press, 2015. Maureen Hall - Waxler, Robert P. The Risk of Reading: How Literature Helps Us to Understand Ourselves and the World. New York: Bloomsbury, 2014. Gae Lyn Henderson--Goodson, Ivor, and Scherto Gill. Critical Narrative as Pedagogy. New York: Bloomsbury, 2014. Connecting Christy Wenger—Risks and Rewards of Purposeful Vulnerability Christina Martorana - Embracing Vulnerability in Teaching Jacquelyn E. Hoerman-Elliot - Writing as a Sea of Oms: A “This I Believe” Essay for Contemplative Writing in First-Year Composition Beth Godbee and Adrianne Wojcik - Decoding Each Other through Coding: Sharing Our Unlikely Research Collaboration Laurence Musgrove—Dress Up Laurence Musgrove—Trees